Insoluble dietary fiber does not affect the ability of phytase to release phosphorus from phytate in the diet of nursery pigs() - Acosta, Jesus A (J Anim Sci, 2019)
Phytase is added to swine diets to improve the utilization of phytate-bound P in swine diets. This provides financial and environmental benefits to the pig industry. However, it is unclear if phytase works equally well in all dietary circumstances. The objective of this experiment was to determine if insoluble fiber affects the efficacy of the phytase enzyme in nursery pigs when fed diets limiting in P content. A total of 480 pigs (initial BW 5.48 ± 0.14 kg) were blocked by BW and randomly assigned (10 pigs per pen) to treatment within the block. A common nutrient-adequate diet was fed from days −14 to −5, and two basal P deficient diets (either a corn-soy diet containing 0.16% standardized total tract digestible [STTD] P [low insoluble fiber [LF]], or a corn-soybean meal plus 20% corn bran containing 0.14% STTD P [high insoluble fiber [HF]]) were fed from days −5 to 0 to acclimate pigs to a P deficient diet. From days 0 to 21, pigs received eight dietary treatments (six pens per treatment: n = 6). Experimental diets consisted of LF supplemented with one of four levels of added phytase (0, 109, 218, and 327 phytase units [FTU]/kg; Quantum Blue 5 G, AB Vista, Wiltshire, United Kingdom) expected to provide 0.16, 0.21, 0.26, and 0.31% STTD P, respectively, or HF supplemented with one of the same four levels of added phytase expected to provide 0.14, 0.19, 0.24, and 0.29% STTD P. Titanium dioxide was added to the diet at 0.4% as an indigestible marker. On day 21, one pig representing the average BW for each pen was euthanized, and fibulae were collected and analyzed for bone ash. Fecal samples were collected from each pen on days 19–20. Data were analyzed using PROC MIXED of SAS. There were no interactions between insoluble fiber and phytase for any of the variables evaluated. For days 0–21, adding phytase increased ADG (P < 0.001) with the response being linear (P < 0.001), whereas insoluble fiber decreased ADG (P = 0.033). There were no effects of phytase or insoluble fiber on ADFI (P = 0.381 and P = 0.632, respectively). Phytase improved G:F ratio (P < 0.001) with the response being linear (P < 0.001). Insoluble fiber tended to decrease G:F ratio (P = 0.097). Phytase increased bone ash (P = 0.005) with the response being linear (P = 0.001), but there was no effect of insoluble fiber (P = 0.949). Phytase did not affect the apparent total tract digestibility of DM, NDF, or ADF (P > 0.050), whereas insoluble fiber decreased the ATTD of DM (P < 0.001), NDF (P < 0.001), and ADF (P < 0.001). In conclusion, the addition of insoluble fiber did not affect the ability of phytase to improve growth performance and bone mineralization in nursery pigs fed a P deficient diet.